Private Net Benefits from Afforesting Marginal Cropland and Shrubland with Cork Oaks in Spain - Ovando, Paola; Campos, Pablo; Oviedo, José L.; Montero, Gregorio (Forest Science, 2010)
We estimate the private net benefits from afforesting marginal shrubland and cropland with cork oaks at two Spanish cork oak sites, Aljibe and Gavarres, in different time horizon frames. The analysis integrates market and nonmarket (landowner amenity) private capital incomes, including government afforestation grants. We apply cost-benefit analysis techniques for estimating the investment present value in the periods analyzed, taking residual values of cork oak woodland into account. The results show that the profitability rate of cork oak afforestation strongly depends on government subsidies. The value of private amenities, at least in Aljibe, seems to be positively affected by the forest area's share of the total estate surface. Thus, an increase in the afforested area would enhance the private amenity annual income with respect to maintaining the original property land's treeless uses. A higher level of private amenities attached to the forest area may imply a reduction in government grants for encouraging cork oak afforestation.
Keywords: cost-benefit analysis; government grants; market incomes; private amenity